Video Blog: Media Pembelajaran Alternatif untuk Melatih Keterampilan Menulis Paragraf bagi Siswa Sekolah Dasar - Angganingrum Shinta Hapsari; Gunarhadi Gunarhadi; Roemintoyo Roemintoyo (Universitas Pendidikan Indonesia Kampus Serang, 2019)
Paragraph writing is important for students in all level. However, it is considered to be difficult for elementary students. This study was set to identify the potential of video blog as an instructional media to enhance writing skill in elementary school. Video blog would function as instructional media in bahasa Indonesia learning. The study included fifth grader students in Marsudirini Elementary Schol and Widya Wacana. Elementary School. Data was collected via questionnaire. This descriptive study was conducted in the 2019 academic year. Findings showed that the teachers were not using instructional media in the class during bahasa Indonesia learning process in the class. The students were mostly used to watch video blog. The students stated the benefit of watching video blog as having better understanding and comprehension of the content. Video blog has potential to be instructional media in bahasa Indonesia learning in elementary school especially in paragraph writing.